Pengaruh Kemitraan dengan PT Indofood Fritolay Makmur (PT IFM) terhadap Efisiensi Petani Kentang di Kecamatan Pangalengan Kabupaten Bandung Provinsi Jawa Barat - Ratu Rihi, Micha Snoverson; Hartoyo, Sri; Faryanti, Anna (Universitas Brawijaya, Indonesia, 2014)
The main objective of this study is to analyze the technical, allocative, and economic efficiencies. In order to that, the study used primary data collected from 80 potato farmers. Using the stochastic frontier analysis (SFA), the results showed that the technical, allocative, and economic efficiencies of the farmers are 0.71, 0.51, and 0.36, respectively. Therefore, if farmers could increase their efficiencies to the highest levels, the cost could be reduced for about 28%, 35%, and 38%, respectively. The model also used a dummy variable to distinguish partnership with PT IFM. It is showed that partnership reduced farmers allocative inefficiency. Otherwise, it increased the technical and economic inefficiencies. Another dummy variable ofpotato cultivation training and duration as a member of farmers club lowered all inefficiencies. The results implied that the average technical, allocative, and economic efficiencies of potato farmers who had partnershipwith PT IFM were lower than those who had no partnership.